The homework machine - Gutman, Dan. (New York : Scholastic Inc., 2006)
Four fifth-grade students, a geek, a class clown, a teacher's pet, and a slacker, as well as their teacher and mothers, each relate events surrounding a computer programmed to complete homework assignments.
Ages 8-12.
680
Accelerated Reader AR
Maine Student Book Award list 2007-2008
Kennebec Valley Book Award list, 2007-2008
Keywords: Homework -- Fiction; Cheating -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction; Arizona -- Fiction